Isopoda (crustacea) from the Levantine sea with comments on the biogeography of mediterranean isopods - CASTELLÓ, JOSÉ; BITAR, GHAZI; ZIBROWIUS, HELMUT (Mediterranean Marine Science, 2020)
This study focuses on the isopod fauna of the eastern Mediterranean, mainly from the waters of Lebanon. Ninety-five samples containing isopods were obtained by scuba diving (depths 0 to 44 m) at 32 stations along the coast of Northern Cyprus, Syria, and Lebanon. The substrates most frequently sampled were caves, vertical walls, and calcareous algae crusts or build-ups. A total of 502 individuals were studied, belonging to 28 species, included in 20 genera, nine families, and three suborders. Four new species from this collection (Atarbolana beirutensis, Cirolana bitari, Cirolana zibrowiusi, Mesanthura pacoi) have already been published. Brief diagnoses and illustrations were included. The collection studied here consists mostly of Mediterranean species, some already known in the area. Ten (eleven, when cf. species is confirmed) are new records in the Levantine Sea (Apanthura addui, Cirolana manorae, Cymodoce fuscina, Cymodoce pilosa, Elaphognathia bacescoi, Gnathia illepidus, Gnathia inopinata, Heptanthura cryptobia, Kupellonura serritelson, Metacirolana rotunda, Pseudocerceis cf. seleneides). Of them, three (four, when cf. species is confirmed) are new records in the Mediterranean Sea (Apanthura addui, Cirolana manorae, Metacirolana rotunda, Pseudocerceis cf. seleneides). Eight species (28.5%) can be considered as non-indigenous (Apanthura addui, Cirolana manorae, Cymodoce fuscina, Metacirolana rotunda, Paracerceis sculpta, Paradella dianae, Pseudocerceis cf. seleneides, Sphaeroma walkeri). This manuscript also provides an inventory of the known Mediterranean isopod fauna (excluding Epicaridea, Oniscidea, and brackish water Aselloidea), which totals 295 species. The isopod fauna of various subregions of the Mediterranean, the Suez Canal, and the Red Sea / Gulf of Aden is compared, and the transit of species through the Suez Canal is discussed. The list of non-indigenous species in the Mediterranaean Sea is updated to 23.